Effect of oral administration of streptomycin on the mortality of guinea pigs inoculated with a virulent strain of Salmonella Typhimurium - Espinoza T., Miguel (2023)
The present study aims to obtain data that facilitate the design of an animal model that replicates salmonellosis produced by the serovar Typhimurium under experimental conditions by a single dose of streptomycin 50 mg orally 24 hours prior to the challenge with three concentrations of a virulent strain of Salmonella Typhimurium. Female guinea pigs (n=58) were used, distributed in 6 treatment groups of 8 animals each (3 groups to which streptomycin was administered prior to the challenge and 3 groups that were only challenged) and 2 control groups of 5 animals each (1 group treated with streptomycin and unchallenged and another untreated and unchallenged). The doses of the inoculum were 107, 108, 109/ml of S. Thiphimurium per group, respectively, and the animals were monitored for 30 days. Collective stool samples per group were collected to determine the excretion time of S. Typhimurium by qPCR. A necropsy was performed on the animals that died, as well as those that survived at the end of the study, taking samples of intestine, liver and lung for histopathological analysis and of intestine, lung, spleen, liver and gallbladder for microbiological isolation. Challenged animals that previously received streptomycin had a higher mortality rate and frequency of macroscopic and microscopic lesions, lower feed consumption, lower final weight, as well as a greater amount and time of excretion of S. Typhimurium in the feces compared to the animals of the non-streptomycin treated group and challenged.